Psalms 60-150 - Kraus, Hans-Joachim; (1918-2000) (U.S.A, 1989)
This is the final volume in Wilberger's comprehensive treatment of Isaiah 1-39. In addition to verse-by-verse commentary, the author provides a systematic overview of the entire Book of Isaiah. This `introduction` to Isaiah covers: the book and the text, the formation of Isaiah 1-39, the prophet Isaiah and his religious roots, the theology of post-Isaianic materials, language and forms of speech in Isaiah, and a listing of recent Isaiah scholarship.
Keywords: Bible -- Psalms, LX-CL